2017
DOI: 10.1007/s00345-017-2131-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-use flexible ureteropyeloscopy: a systematic review

Abstract: Single-use FURS demonstrates comparable efficacy with reusable FURS in treating renal calculi. Further studies on clinical efficacy and cost are needed to determine whether single-use FURS will reliably replace its reusable counterpart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…That study also found that the overall, mean procedure time was 10 min shorter in cases using the LithoVue . A recent systematic review found no difference in operative time, stone clearance or complications between disposable and reusable fURS …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…That study also found that the overall, mean procedure time was 10 min shorter in cases using the LithoVue . A recent systematic review found no difference in operative time, stone clearance or complications between disposable and reusable fURS …”
Section: Introductionmentioning
confidence: 81%
“…3 A recent systematic review found no difference in operative time, stone clearance or complications between disposable and reusable fURS. 18 There are currently no in vivo studies comparing the performance of the different types of single-use fURS. To date, just two studies have compared single-use scopes with modern reusable video fURS.…”
Section: Introductionmentioning
confidence: 99%
“…Polyscope TM performed adequately but was unable to provide the same SFR for lower pole stones than reusable scopes 9 . Newer scopes provide similar maneuverability and clinical efficacy to reusable scopes with equal low complication rates and are now part of the urology routine worldwide 6,10,13,17,18,20,[22][23][24]42 . The trial by Usawachintachit et al 10 could even have shown superiority with LithoVue TM compared to a reusable scope if a larger sample size was included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reinforce the need for frequent audits of reprocessing practices and highlight that the clinical implications of residual contamination and viable microbes found on sterilized ureteroscopes are still unknown. In that sense, no study has ever shown an inferior rate of urinary tract infection after flexible ureteroscopy with the employment of single-use devices 6,7,10 . Therefore, the initial fear of cross infection with reusable scopes is not supported by existing literature and this is only a potential benefit from single-use scopes which has yet to be proven in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation